Planos de nutrição utilizando lactose em dietas para leitões desmamados em diferentes idades - Dalton Cesar Milagres Rigueira (2014)
In order to determine sequences of lactose levels in diets for weaned piglets in different ages, three experiments were performed, where each weaning age corresponded to one experiment (18, 21 and 24 days). It were used 192 piglets for each experiment, distributed in a randomized block designed with four lactose levels, six replicates and eight piglets in each experimental unit, totaling 48 piglets for treatment. In the first period post weaning, from weaning to 35 days, the piglets received pre-initial II feed containing 0,0; 5,0; 10 and 15% of lactose and the levels have reduced by half in the second period (from 36 to 49 days), at initial I, however combined to constitute the sequences of lactose of 0,0:0,0; 5,0:2,5; 10:5,0 and 15,0:7,5. At 49 days, in the morning, were separated two animals per stalls, those representing the average weight of the bay, these piglets were contained and removed 10 ml of blood from the jugular vein for measuring the blood level of urea and haptoglobin. At 35 days of age, there was a linear effect on the final weight, average daily feed intake and average daily weight gain due to the increased inclusion of lactose in the diets with weaning done in the three ages, while the feed conversion showed a quadratic effect only in the weaned piglets at 18 and 21 days of age. At 49 days, when the treatments were compared to the lactose-free treatment (0,0:0,0%), statistical difference was observed on the final weight of all piglets fed with lactose diets (P<0,05) and weaned at 18 days, and only in piglets that consume feed containing 15:7,5% of lactose weaned at 21 days. In the piglets weaned at 18 and 21 days, the average daily feed intake differed on who received feed containing 10:5,0 and 15:7,5% of lactose (P<0,05), and the average daily weight gain was higher only in piglets that received a diet containing 15:7,5% of lactose (P<0,05). No statistical differences were observed regarding the feed conversion (P>0,05). The serum urea and haptoglobin concentration showed statistical differences (P>0,05) in the piglets weaned at 21 days which consumed feed containing 15:7,5% of lactose. Effect was observed in absolute liver weight (P<0,05) of piglets who received the treatment with 15:7,5% of lactose which were weaned at 18 and 21 days. In relation to intestinal microstructure, only the piglets which received feed with 15:7,5% of lactose which were weaned at 18 days differed statistically from lactose-free treatment, obtaining greater measures of villi (P<0,05). The crypt depth against villus height/crypt depth of the jejunum were not influenced by any of the nutritional plans studied (P>0,05). No statistical difference was observed in any parameter studied in weaned piglets at 24 days of age. It is concluded that the sequence of lactose being used for weaned piglets at 18 and 21 days of age is 15:7,5%